PEMBANGUNAN INDUSTRI MUZIK IBAN DARIPADA TAHUN 2008 HINGGA 2015 - WINSTON, DAMY (Universiti Malaysia Sarawak (UNIMAS), 2016)
This study is a study of Iban music industry from 2008 to 2015. This study is to assess progress and identify strategies used in developing the Iban music industry. This study is based on qualitative methods, that using the interview method to get excellent data to answer all the objectives that have been set. All data results from the interviews will be transcribed and then presented in the form described in descriptive method to facilitate the delivery to facilitate the understanding of the reader. The researchers interviewed a total of 5 people intel informant- consisted of Mr. Isa Lee is a teacher, writer Iban music industry-related articles, and the Deputy Chairman of the Association of Artistes and Dayak Cultural Kuching, Mr. Brown Sang Lagan was a teacher and as chairman Dayak Artist and Musician Association (DAMA), Mr. Romie Austin Chai is a Artistes, Mr. Mohamad Rizal Bin Kassim is Artistes Music Iban new in Iban music industry and as the owner of a music studio in Sungai Merah, Sibu, Sarawak and Mr. Snowdan Lawan is a politician and patron of Dayak Artists and Musicians Association (DAMA).